Men with unilateral Achilles tendinopathy have impaired balance on the symptomatic side. Issue 5 (May 2018) - Scholes, M.; Stadler, S.; Connell, D.; Barton, C.; Clarke, R.A.; Bryant, A.L.; Malliaras, P
Abstract: Objectives: To investigate single leg standing balance in males with mid-portion Achilles tendinopathy (AT). Design: Cross sectional case study. Methods: Centre of pressure (COP) path length was measured using a Wii Balance Board (WBB) in 21 male participants (20–60 years) with unilateral mid-portion AT during single-limb standing on each limb with eyes open and closed. Ultrasound imaging of both Achilles tendons was also performed by one blinded assessor, and the anteroposterior (AP) thickness and presence of pathology was determined. Comparisons were made between symptomatic and asymptomatic sides for key outcomes, and correlation between COP path length and variables of interest were investigated. Results: Symptomatic Achilles tendons demonstrated significantly increased AP tendon thickness (p < 0.001). Participants with AT demonstrated increased COP path length (sway amplitude) on their affected side during the eyes closed task (p = 0.001). Increased tendon thickness was associated with increased sway amplitude during the eyes open task on both the affected (rho = 0.44, p = 0.045) and unaffected sides (rho = 0.62, p = 0.003). Conclusions: In males with AT, single-leg standing balance with eyes closed is impaired on the symptomatic side. This indicates that neuromuscular deficits affecting functional ability may be present in people with AT during more challenging balance activities. It is unclear if this deficit precedes the onset of symptoms, or is a consequence of tendon pain. Work is now needed to understand the mechanisms that may explain standing balance deficits among people with AT.